ANALISIS KEBIJAKAN PUBLIK TENTANG OPERASI PLASTIK DALAM PERSPEKTIF HUKUM ISLAM - Saputra, Ahmad Dani Agustian; Reyhana, Reyhana; Amin, Fadli; Qosim, Agus Maulana (Journal Education and Government Wiyata, 2025)
Reconstructive plastic surgery is permitted (mubah) if it is intended to correct congenital defects, restore bodily functions due to accidents, or for other medical reasons. Plastic surgery performed to beautify the body without medical necessity is considered haram because it falls into the category of changing Allah's creation as explained in Q.S. An-Nisa (4): 119. The views of scholars, such as Muhammadiyah and Nahdlatul Ulama, emphasize that this type of surgery is only permitted in emergency situations. Therefore, plastic surgery in Islam must be understood based on its intention, purpose, and impact on human honor and welfare.